The Importance of Creativity in the Sportification of Breakdance - Yang, Zhi; Bai, YuJie; Wei, MingTao (Frontiers in Education, 2022)
Many historical works have attempted to reveal the process of the sportification of physical activity that originated in the eighteenth century. The process of sportification can be divided into three basic mechanisms: The institutionalization of practices, the formalization of standards, and the specialization of roles. Marginalized and discriminated lower-class American youths first used breakdancing to express their emotions. Nowadays, it has been announced by the International Olympic Committee as part of the Paris 2024 Olympic program in Paris, France. Therefore, this change may also further the specialization of breakdance teaching. In addition, this mini-review believes that it is necessary for breakdancing teachers, students, and judges to have a clear understanding of creativity, as it is often used as an essential scoring criterion in breakdancing competitions. This mini-review also shows the origins and evolution of breakdance. Cipher as a form of artistic communication produced the domino effect, which promoted the widespread popularity of breakdance worldwide. Creativity has also driven the evolution of breakdance moves. Finally, this article discusses the advantages and examples of the Four C models and suggests a set of methods for breakdance teachers to foster creativity in breakdance students.